2003
DOI: 10.1046/j.1442-2026.2003.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of a verbal numeric rating scale with the visual analogue scale for the measurement of acute pain

Abstract: Objectives: To test the agreement between the visual analogue scale (VAS) and a verbal numeric rating scale (VNRS) in measuring acute pain, and measure the minimum clinically significant change in VNRS. Methods: Patients scored their pain by the VAS and the VNRS, then re‐scored their pain every 30 min for up to 2 h. Patients also recorded whether their pain had improved or worsened. Agreement between scores was evaluated, and where patients scored their pain as ‘a bit worse’ or ‘a bit better’ the mean change i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
197
2
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 235 publications
(219 citation statements)
references
References 15 publications
10
197
2
4
Order By: Relevance
“…This scale can be used with adults and children (> 9 years old) and in all patients able to use numbers to rate the intensity of their pain. 26 The significance of the verbal numeric scale was studied by Holdgate et al 27 in 2003, and the authors concluded that VNS is a valid instrument to assess changes in pain intensity…”
Section: Measurementsmentioning
confidence: 99%
“…This scale can be used with adults and children (> 9 years old) and in all patients able to use numbers to rate the intensity of their pain. 26 The significance of the verbal numeric scale was studied by Holdgate et al 27 in 2003, and the authors concluded that VNS is a valid instrument to assess changes in pain intensity…”
Section: Measurementsmentioning
confidence: 99%
“…Although VAS is generally regarded as a valid and reliable tool for chronic pain measurement, 29 these scores could conceivably reflect long-term memory or other inaccuracies, and correlation between VNRS and VAS has been imperfect in previous studies. 30 Results of patency may influence VAS. A cognitive assessment such as a pain score may be highly influenced by other cognitive factors.…”
Section: Discussionmentioning
confidence: 99%
“…The instrument is well established and its scores have been reported to correlate strongly (r = 0.95) with scores on a visual analog scale in an adult population with acute pain. 18 The VNRS has been used in previous studies of lung transplant recipients. 19 Patients are more familiar with the VNRS, which is commonly used in clinical practice to assess pain intensity.…”
Section: Methodsmentioning
confidence: 99%